STUDENTS’ PERCEPTION ON THE USE OF A MASSIVE OPEN ONLINE COURSE FOR PARASITOLOGY: A PRELIMINARY STUDY - Utomo, Prattama Santoso; Kusumasari, Rizqiani Amalia; Murhandarwati, Elsa Herdiana; Widyandana, Doni (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2023)
Background: The COVID-19 pandemic had a significant impact on medical education globally. The learning process has been shifted to online learning to ensure health and safety measures. Online learning approaches and applications are also established rapidly, including the Massive Open Online Course (MOOC), which can support learning in many topics and facilitate a large number of students effectively and efficiently. Department of Parasitology and Department of Medical Education and Bioethics, Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada developed the Central Nervous System (CNS) Parasitic Infection module as an online learning for both undergraduate and postgraduate levels.Aims: The study aimed to evaluate and explore students’ perception of the CNS Parasitic Infection online module development in an MOOC format.Methods: This is an evaluation study using an explorative qualitative approach. The pilot implementation of the CNS Parasitic Infection module was evaluated using in-depth interviews with ten (10) students of the Master in Tropical Medicine and the Master in Biomedical Science programs. The participants were requested to share their learning experience on the module, and their suggestions for module improvement. The interviews were conducted online using Zoom. The interview transcripts were analyzed using thematic analysis.Results: Implementing the CNS Parasitic Infection module using MOOC asynchronous approach received both positive and negative responses from participants. A total of 6 themes were identified from participants, for instance, learning outcomes achievement, interactive e-case design, learning flexibility, course timing, network issues, and the need for learning directions.Conclusion: CNS Parasitic Infection can be delivered to students using an asynchronous MOOC format. Students’ outcomes achievement was sufficient using this method, and overall, students appreciated the implementation of the program.